Analisis Perancangan Webtoon Sebagai Media Promosi Kuliner Seafood Khas Batam Menggunakan Metode Design Thinking - Harley Fernando; Deli Deli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Webtoon is a complex system designed or created through media in the form of comics and digitally which is read using the scrolling method by readers. The study was conducted by developing a webtoon to introduce Batam's unique seafood cuisine to Indonesian webtoon readers, especially in the city of Batam with the primary age range of 17-24 years. The data analysis method used is the 5W1H qualitative method and the design method used is Design Thinking which has 5 stages in the form of empathize, define, ideate, prototype, and test. The results of the webtoon design were then analyzed using a qualitative approach, namely by distributing questionnaires and taking samples using purposive sampling techniques. The results of the study on the webtoon design got a positive response from the respondents and can be categorized as good and interesting even though there are still some deficiencies in it. The webtoon designs are published on LINE Webtoon with one episode in total.